THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING BIOLOGY - HALIMOVA MOHIGUL RUSTAMOVNA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The desire for self-education is a distinctive feature of a modern teacher. A modern teacher today becomes the organizer of the process of obtaining knowledge using modern information technologies, contributing to the self-education and self-realization of students. The use of computer technology in biology lessons is a significant update to the content of biological education, and therefore the teacher must be competent in the field of computer technology.